ASSURANCE LAPORAN KEBERLANJUTAN: DETERMINAN DAN KONSEKUENSINYA TERHADAP NILAI PERUSAHAAN - Jeska Almira Indyanti; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2017)
This study aims to examine the effect of determinants of assurance statement on sustainability report and the impact on firm value. Stakeholder Theory and Signalling Theory are adopted to construct the hypotheses. The population is nonfinancial companies that published sustainability report over 2012-2014. Using purposive sampling, 70 samples are obtained. This research used two analysis models. Logistic regression is used to analyze the determinants on assurance statement, meanwhile multiple regression is used to analyze its consequence on firm value. The result shows that there is positive and significant effect of environmentally sensitive industry and sustainability department to assurance statement. However, there is evidence that firm size and scope of disclosure not affecting the assurance statement. Furthermore, there is evidence that companies providing assurance statement are more likely to have higher firm value.